MON-LB112 Socioeconomic Status, Literacy, and Sex Differences in the Progression of Retinopathy in Patients With Type 2 Diabetes in Tokyo, Japan - Emoto, Naoya (J Endocr Soc, 2020)
Socioeconomic status has profound effects on glycemic control and diabetic complications in patients with type 2 diabetes. Sex differences are one of the most important factors in socioeconomic status and may vary among countries or areas. The study aim was to determine if sex differences are associated with glycemic control and diabetic complications in Tokyo, Japan, one of the most educated countries in the world. This study initially enrolled 3307 patients treated from 2017 to 2019 at the medical school hospital located in Tokyo. All enrolled patients were asked to complete behavioral and socioeconomic surveys. A total of 276 type 2 diabetic patients (175 males, age 64.1 ± 0.88 y, disease duration 15.2 ± 0.78 y, mean ± SE y; 101 females, age 64.0 ± 1.1 y, disease duration 15.6 ± 1.01 y) agreed to participate in the study. The survey questionnaire has been previously reported in detail (Patient Preference and Adherence, 10:2151-2162, 2016). The questionnaire attempted to determine estimations of risk preference regarding things like lottery gambling and accident insurance. After reviewing the patients’ answers, however, it became clear that some were illogical, which suggested that these patients did not understand the context of the questions, the hypothetical economical situations, or even the instructions, probably because of lower literacy skills. Thus, we labeled these patients as the unreasonable (UR) group (n = 81), and the patients who provided appropriate answers, even if extremely risk averse or risk loving, were labeled as the reasonable (R) group (n = 195). The prevalence of UR answers generally increased with age (<50 y, 16%; 50-64 y, 10%; 65-74 y, 37%; ≥75 y, 64%) (p < 0.0001). After age adjustment, there was a significant correlation between the UR answers and educational attainment in both sexes. The prevalence of UR answers was significantly higher in females (38.6%) than in males (24%) (p < 0.01), which may be partly because the average number of educational years was lower for females than for males (males, 13.8 y; females, 12.9 y; p < 0.05), but both averages are very high among all countries. The prevalence of retinopathy was significantly higher in the UR than the R group in males (p < 0.05), but not in females. Job and economic status were not associated with prevalence of retinopathy. These results suggest that effects of literacy skills on progression of diabetic retinopathy may be sex dependent. Although the mechanism underlying this finding is unknown, sex may be an important biological factor beyond socioeconomic status in highly educated high-income countries.